Securing the Website Login System with the SHA256 Generating Method and Time-based One-time Password (TOTP) - Iman Permana; Mardi Hardjianto; Kiki Ahmad Baihaqi (SYSTEMATICS, 2020)
Security to enter a system has a very important role because as the main entrance to access data sources. But often lack the attention of the owners and managers of information systems. To reduce these weaknesses, one method that is widely used today is to use One-Time password, which is where the password we have becomes dynamic, meaning that at a certain time the password is always changing, the positive side is that it makes it difficult for others to steal our passwords because besides representative passwords that are difficult to understand and passwords are always changing. This study discusses One-Time Password installed on a mobile device where the password is randomized using a combination of two algorithms, namely SHA256 and Time-based One Time Password. The development of this login method can reduce the level of theft of passwords owned by users who are entitled to access information sources.